Ultimate terrorists - Stern, Jessica (London, 1999)
As bad as they are, why aren't terrorists worse? With biological, chemical and nuclear weapons at hand, they easily could be. Jessica Stern argues that the nuclear threat of the Cold War has been replaced by the more imminent threat of terrorist attacks with weapons of mass destruction. According to Stern, several factors increase the probability of a major incident. Most important is the emergence of a new breed of terrorists - violent, right-wing extremists, apocalyptic groups, and millenarian cults, all less constrained than their predecessors by traditional ethics or political pressures and more capable of recruiting scientists. Such scientists, including unemployed Societ weapons experts, and the dissemination of know-how about nuclear, biological and chemical weapons in books and on the Internet heighten the risk. Written from an insider's perspective, this text depicts a not very distant future in which both independent and state-sponsored terrorism using weapons of mass destruction could actually occur. But Stern also holds out hope for new technologies that might combat this trend, and for legal and political remedies that would improve public safety without compromising basic constitutional rights.
Keywords: Terrorism